Empty mansions : the mysterious life of Huguette Clark and the spending of a great American fortune - Dedman, Bill; Newell, Paul Clark, Jr (Ballantine Books Trade Paperbacks, 2014)
When Pulitzer Prize-winning journalist Bill Dedman noticed a property listing for a grand estate that had been unoccupied for nearly sixty years, he stumbled into one of the most surprising American stories of the nineteenth and twentieth centuries. Empty Mansions is a rich tale of wealth and loss, complete with copper barons, Gilded Age opulence, and backdoor politics. At its heart is a reclusive 104-year-old heiress named Huguette Clark. Dedman has collaborated with Huguette's cousin, Paul Clark Newell, Jr., one of the few relatives to have had frequent conversations with her, to tell a fairy tale in reverse: the bright, talented daughter who is born into an almost royal family of amazing wealth and privilege, yet who secrets herself away from the outside world. Empty Mansions reveals a complete picture of the enigmatic Huguette Clark, heiress to one of the greatest fortunes in American history, a woman who had not been photographed in public since the 1920s.